2006
DOI: 10.1021/bm060574h
|View full text |Cite
|
Sign up to set email alerts
|

Candida antarctica Lipase B-Catalyzed Synthesis of Poly(butylene succinate):  Shorter Chain Building Blocks Also Work

Abstract: Lipase catalysis was successfully employed to synthesize high molecular weight poly(butylene succinate) (PBS). Attempts to copolymerize succinic acid with 1,4-butanediol were unsuccessful due to phase separation of the reactants. To circumvent this problem, monophasic reaction mixtures were prepared from diethyl succinate and 1,4-butanediol. The reactions were studied in bulk as well as in solution. Of the organic solvents evaluated, diphenyl ether was preferred, giving higher molecular weight products. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 21 publications
3
123
0
5
Order By: Relevance
“…It has been reported that Novozyme 435 could catalyze reactions at higher temperatures up to 90 8C. 24 However, the epoxide product is not stable at higher temperatures. As shown by the HPLC chromatograms in Figure 1, 100% conversion of oleic acid can be achieved within 5 h at 40 8C.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Novozyme 435 could catalyze reactions at higher temperatures up to 90 8C. 24 However, the epoxide product is not stable at higher temperatures. As shown by the HPLC chromatograms in Figure 1, 100% conversion of oleic acid can be achieved within 5 h at 40 8C.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that the reaction times required to prepare these polymers were not excessively long, all subsequent polymerizations were performed using 10 wt% Novozyme 435 Ò . Since the loading of CALB in the Novozyme 435 Ò preparation is only 10 wt%, the actual amount of CALB used in the reactions is 1 wt% [27].…”
Section: Synthesis Of Poly(18-octanediol-co-sorbitol Adipate)mentioning
confidence: 99%
“…[33][34][35][36][37] In recent years, enzymatic synthesis of sustainable polyesters from biobased monomers has attracted much attention. 5,32 Plenty of biobased polyesters have been readily prepared via enzymatic polymerization, e.g., succinate-based aliphatic polyesters, [38][39][40] 1,4 : 3,6-dianhydrohexitol-based polyesters, 41,42 vegetal oilbased polyesters, 43 sugar derived diol-based polyesters, 44,45 etc. Recently we successfully synthesized a series of renewable 2,5-bis(hydroxymethyl)furan-based polyesters by two-stage enzymatic polycondensation in diphenyl ether.…”
Section: Introductionmentioning
confidence: 99%